The Effect of Using Audio Visual Media and Motivation on Teacher Performance in Public Elementary Schools in Ilir Timur II District, Palembang City - M Adji Purnomo; Syarwani Ahmad; Mahasir Mahasir (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
This study aims to identify and analyze: (1) the relationship between the use of audio-visual media and teacher performance; (2) The relationship between teacher motivation and teacher performance; (3) The relationship between the use of audio-visual media and teacher motivation together on teacher performance. A double linear regression quantitative research method was used to achieve this goal. This research was conducted in Public Elementary Schools in Ilir Timur II District, Palembang, with 64 teachers as respondents—data collection techniques using questionnaires and documentation. The validation test uses validity by looking at the Pearson correlation value. Meanwhile, the reliability test uses Cronbach's Alpha. Analysis tests using normality, heteroscedasticity, multicollinearity, and linearity tests. Test the hypothesis using the T, F, and R 2 tests. The results showed that: (1) there is a positive and significant relationship t table 1.99773, (2) there is a positive and significant relationship between teacher motivation and teacher performance with a value of t table 5.816 > t table 1.99773, (3) there is a positive and significant relationship between the use of audio-visual media and teacher motivation with teacher performance with a correlation value of 0.713 with a percentage of 71.3%, while 28.7% was determined by other factors not mentioned in this study.